UMP targets 4 strategic objectives towards the best technological university by 2050 - UMP, PNC (2020)
Universiti Malaysia Pahang (UMP) has laid the foundation in achieving excellence for UMP Strategic Plan 2021–2025 by targetting four main objectives, which are (1) producing holistic community-driven graduates through high-level Technical and Vocational Education and Training (TVET), (2) communitising technology, (3) generating new advanced technologies via research initiatives, and (4) achieving financial and best practices sustainability.